2011
DOI: 10.1136/bmjopen-2010-000023
|View full text |Cite
|
Sign up to set email alerts
|

A systematic mapping review of effective interventions for communicating with, supporting and providing information to parents of preterm infants

Abstract: Background and objectiveThe birth of a preterm infant can be an overwhelming experience of guilt, fear and helplessness for parents. Provision of interventions to support and engage parents in the care of their infant may improve outcomes for both the parents and the infant. The objective of this systematic review is to identify and map out effective interventions for communication with, supporting and providing information for parents of preterm infants.DesignSystematic searches were conducted in the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 69 publications
6
123
0
17
Order By: Relevance
“…[15,16] Despite satisfaction with overall care, many parents were anxious and felt helpless and unable to protect their baby from pain, and this underlying perception about pain is consistent with other pain literature. [17,18] All families who said they were able to cope attached great importance to a timely meeting with the clinical team at the start of treatment.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…[15,16] Despite satisfaction with overall care, many parents were anxious and felt helpless and unable to protect their baby from pain, and this underlying perception about pain is consistent with other pain literature. [17,18] All families who said they were able to cope attached great importance to a timely meeting with the clinical team at the start of treatment.…”
Section: Discussionsupporting
confidence: 62%
“…It has been suggested that greater emphasis on continuity with communication might improve parents' ability to cope. [15,16] Breast feeding and skin to skin care are both perceived by parents as important to co-regulate with their infant and development of bonding. [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence, primarily in newborn and high-risk adult populations, that postdischarge home nurse visits or phone calls can improve outcomes such as decreased health care utilization. [35][36][37][38][39][40][41][42] Such evidence, in combination with our findings, reinforces the need for further study of visits or calls that are tailored to meet the needs of families after hospital discharge. Determining their impact on both family-centered outcomes in addition to health care utilization is critical.…”
Section: Figurementioning
confidence: 54%
“…The disease or clinical complications of the newborn that arises then, cause much suffering 4,6,7,15 , requiring radical and inevitable changes in the family routine 6,16,17 . A goal to be considered by the health team in the treatment of hospitalized infants is to reduce the anxiety of parents by offering support, answering questions, helping them to express their feelings 17 .…”
Section: Discussionmentioning
confidence: 99%